DAMPAK BENEFITS DAN CHALLENGES IOT ADOPTION TERHADAP SUPPLY CHAIN PERFORMANCE DAN ORGANIZATIONAL PERFORMANCE - Armando Armando; Sri Vandayuli Riorini (Universitas Kuningan, 2023)
AbstrakDi Indonesia, industri manufaktur merupakan pendukung penting pembangunan ekonomi. akibatnya Teknologi mutakhir dan terbaru seperti Internet of Things (IoT) diharapkan berdampak besar pada bisnis dan Supply Chain Performance (SCM). Penelitian tentang dampak adopsi IoT pada rantai pasokan dan Tindakan organisasi relatif jarang . Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui hubungan antara manfaat dan tantangan adopsi IoT dan kinerja organisasi. Selain itu, penelitian ini mengkaji peran mediasi kinerja rantai pasok dalam hubungan interpersonal. Di antara manfaat dan tantangan adopsi IoT dan kinerja bisnis. Populasi penelitian ini terdiri dari 107 responden, rangkaian kuesioner disebar melalui Google form yang sesuai dengan lima persen dari tingkat respons. Pemodelan Persamaan Struktural (SEM) digunakan untuk mengevaluasi semua hipotesis penelitian. Hasil dari pekerjaan ini mendukung semua hipotesis yang diajukan Singkatnya, industri manufaktur Indonesia perlu mendapatkan keuntungan lebih akan tetapi IoT malah terus menghadapi tantangan. Studi ini dapat menjadi pedoman bagi perusahaan manufaktur dalam mengambil keputusan tentang adopsi IoT. Kata kunci: benefits of iot adoption; challenges of iot adoption; supply chain performance; organizational performance AbstractIn Indonesia, the manufacturing industry is an important supporter of economic development. as a result Cutting-edge and latest technologies such as the Internet of Things (IoT) are expected to have a major impact on business and Supply Chain Management (SCM). Research on the impact of IoT adoption on supply chains and Organizational actions are relatively rare. Therefore, the purpose of this study is to investigate the relationship between the benefits and challenges of IoT adoption and organizational performance. In addition, this research examines the mediating role of supply chain performance in interpersonal relationships between the benefits and challenges of IoT adoption and business performance. The population of this study consisted of 107 respondents, a series of questionnaires were distributed via the Google form. which corresponds to five percent of the response rate. Structural Equation Modeling (SEM) was used to evaluate all research hypotheses. The results of this work support all the hypotheses put forward. In short, the Indonesian manufacturing industry needs to gain more profits but IoT continues to face challenges. This study can be a guideline for manufacturing companies in making decisions about IoT adoption. Limitations and recommendations for future research are highlighted.Keyword: Benefits of IoT Adoption; Challenges of IoT Adoption; Supply Chain Performance; Organizational Performance